Combinatorial use of communication technologies in organizations. (1st August 2019) - Zhu, Yaguang
Abstract : Purpose: The purpose of this paper is to critique and extend contemporary scholarship on information and communication technologies (ICTs). This paper argues that the focus on the selection and use of a single communication medium limits the understanding of current ICT use in organizations. A combinatorial perspective is needed to capture the complexities of multiple ICTs use for achieving communication goals and completing tasks. Design/methodology/approach: This paper addresses the trending phenomenon of combinatorial use of ICTs by offering a critical review of the theoretical studies and empirical research in scholarly books and journals and deriving novel theoretical research questions that set the stage for future studies. Findings: This paper identifies how combinatorial ICT use as a perspective that uniquely elucidates ICT use in organizations, clarifies key terms used in previous research and proposes theoretical and operational recommendations for researchers and corporate practitioners who are interested in studying the combinatorial use of ICTs. Originality/value: This paper highlights that understanding the combinatorial use ICTs in complex work environments could have significant implications for productivity and efficiency of individuals and corporations. This paper serves as a catalyst for on-going research conversations regarding combinatorial ICT use, while assisting organizational communication researchers and practitioners in describing, theorizing and advancing ICT implementation, use and outcomes.